The Effects of Two Different Concurrent Training Configurations on Markers of Metabolic Syndrome and Fitness in Women With Severe/Morbid Obesity: A Randomised Controlled Trial - Delgado-Floody, Pedro; Soriano-Maldonado, Alberto; Rodríguez-Pérez, Manuel A.; Latorre-Román, Pedro Ángel; Martínez-Salazar, Cristian; Vargas, Claudia Andrea; Caamaño-Navarrete, Felipe; Jerez-Mayorga, Daniel; Álvarez, Cristian (Frontiers in Physiology, 2021)
Concurrent training (CT), characterised by combining both aerobic and resistance training modalities within the same session, is recognised to improve metabolic syndrome (MetS) markers, but little is known about the effects of different configurations (i.e., order) of these exercise modalities on MetS markers and the interindividual responses. The purpose of the present study was to describe the effects, and the interindividual variability, of 20weeks of two CT configurations (i.e., high intensity interval training (HIIT) plus resistance training (RT), compared with RT plus HIIT) in women with severe/morbid obesity. Overall, 26 women with severe/morbid obesity were assigned either to HIIT+RT [n=14, mean and 95%CI, 45.79 (40.74; 50.83) or RT+HIIT (n=12), 33.6 (25.30; 41.79) years]. MetS-related outcomes were waist circumference (WC, cm), systolic (SBP, mmHg) and diastolic (DBP, mmHg) blood pressure, high-density lipoprotein cholesterol (HDL-c), triglycerides (Tg), and fasting plasma glucose (FPG). Secondary outcomes were other anthropometrics, body composition, lipids, muscle strength, and the six-minute walk test (6Mwt). There were significant differences in the prevalence of nonresponders (NRs) only for WC comparing HIIT+RT 2 (18.1%) vs. RT+HIIT group 5 (50.0%), p<0.0001, but not for SBP 4 (27.2%) vs. 4 (40.0%), DBP 8 (72.7%) vs. 7 (70.0%), FPG 8 (72.7%) vs. 9 (90.0%), HDL-c 7 (63.6%) vs. 8 (80.0%), and Tg 7 (63.6%) vs. 8 (80.0%), all p>0.05. Additionally, the RT+HIIT group showed significant reductions in WC (∆ –3.84cm, p=0.015), SBP (∆ –8.46mmHg, p=0.040), whereas the HIIT+RT group elicited significant reductions only in SBP (∆ –8.43mmHg, p=0.022). The HIIT+RT promoted a lower prevalence of NRs than the RT+HIIT configuration on WC, and overall, there were slightly more beneficial training-induced effects on markers of MetS in the RT+HIIT group compared to the HIIT+RT group.